INDONESIAN SCIENCE EDUCATOR’S RESPONSE TO THE ONLINE LEARNING CAUSED BY COVID-19: DRAWBACKS AND ADVANTAGES - Dessy Nur Amelia (Jurnal Pengajaran MIPA, 2020)
This paper is aimed to analyse of Indonesian science teachers’ perspective regarding the implementation of online learning as an impact of the COVID-19 pandemic. In this study, three science teachers were asked their perspectives about the challenges and benefits of online teaching. The participants perceived obstacles in online learning are insufficient facilities, lack of parents’ engagement, challenges in adapting with new policies at school, impossibility to conduct the hands-on practicum, and a decrease in student enthusiasm to learn. The challenges are mainly caused due to the nature of online learning that requires new skills that are different from face-to-face classroom setting. However, online learning has caused the participants to grow their digital skills aside from having more flexibility in managing their time. This study suggests the importance to provide training for teachers to allow them to teach effectively in online setting.